Occupational radiation dose during fluoroscopy guided interventional procedures at Institut Kanser Negara. (June 2019) - Bohari, A; Hashim, S; Mustafa, S N M
Abstract: Fluoroscopy-guided interventional (FGI) tends to involve long-term procedures that increase the fluoroscopy time and the dose area product (DAP). Therefore, radiation protection is a major concern for interventional radiology staff. This study signifies the occupational and the radiation doses for interventional radiology staff, in particular, non-physician in order to clarify the current dose level for radiographers and nurses. The occupational doses were compared among interventional radiology staff in Institut Kanser Negara (IKN), Putrajaya, Malaysia where 230 patients underwent FGI procedures were observed in one-year. The occupational doses of interventional radiologist (IR), medical officer (MO), radiographer and nurse were recorded using two optically stimulated luminescence dosimeter (OSLD), one worn over and one under their protective aprons. The occupational dose (effective dose) indicated that the IR, MO, radiographer and nurse with double OSLDs were 9.82, 7.91, 6.42 and 6.02 mSv, respectively. The effective dose of IR, MO, radiographer and nurse were 7.63, 7.91, 6.42, 5.66 mSv, respectively using a single OSLD. It has shown a statistically significant difference in the effective dose of double worn OSLDs and one OSLD of ( p < 0.05) for interventional radiology staff. In both methods, IR > MO > radiographer > nurse was the highest effective dose in the interventional radiology staff. However, the occupational dose of single OSLD was found to be lower than double OSLDs. It is highly recommended that interventional radiology staff to use double OSLDs during the FGI procedures in order to determine the occupational dose accurately.